2021
DOI: 10.3390/su13052551
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Synthetic Evaluation of the Critical Success Factors for the Sustainability of Public Private Partnership Projects in China

Abstract: Public Private Partnership (PPP) projects have attracted wide attention from academia and industry over the past 20 years, however, they have been plagued by certain factors. This study identified, classified, and evaluated the success factors that may affect PPP projects for achieving sustainability. First, a list of 32 critical success factors were categorized into 3 groups, then a questionnaire survey was conducted, with 108 responses received from experts, researchers, and PPP project managers in China. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 110 publications
0
18
0
Order By: Relevance
“…Their purpose is usually to identify, classify and evaluate the success factors of PPPs. In a paper [16], the authors conducted a survey with 108 responses from experts, researchers and project managers. The fuzzy synthetic evaluation (FSE) method was then applied and nine most important factors were obtained.…”
Section: Review Of Applied Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their purpose is usually to identify, classify and evaluate the success factors of PPPs. In a paper [16], the authors conducted a survey with 108 responses from experts, researchers and project managers. The fuzzy synthetic evaluation (FSE) method was then applied and nine most important factors were obtained.…”
Section: Review Of Applied Research Methodsmentioning
confidence: 99%
“…At the same time, it is the best model satisfying the p2 criterion. The second-best model satisfying the p2 criterion is the hyperbolic model I with variables 1, 8, 11, 12 (WD7) 16 . Models satisfying criterion p1 do not use variables 3 and 8 (Table 21).…”
Section: Best Regression Models For Value and Number Of Ppp Contractsmentioning
confidence: 99%
“…As a result, positivist tradition was the epistemological perspective in this study. This approach has been widely used to recent construction management and civil engineering literature (Aghimien et al , 2020; Deng et al , 2021; Guribie et al , 2022; Wuni and Shen, 2020)…”
Section: Methodsmentioning
confidence: 99%
“…As a result, positivist tradition was the epistemological perspective in this study. This approach has been widely used to recent construction management and civil engineering literature (Aghimien et al, 2020;Deng et al, 2021;Guribie et al, 2022;Wuni and Shen, 2020) Identification of the study variables The measurement items for the current study were identified from the review of pertinent literature. After a thorough review of literature, 20 potential obstacles to the personalization of knowledge flows were identified in this study, as listed in Table 1.…”
Section: Philosophical Positioningmentioning
confidence: 99%
“…rough the AHP, Xiang et al [13] optimized the influencing factors of VFM evaluation in PPP projects. Deng et al carried out fuzzy comprehensive evaluation (FCE) to identify the key success factors of PPP projects [14]. Cui et al [15] confirmed and verified the relationship between VFM drivers of PPP projects through questionnaire survey and scanning electron microscopy (SEM).…”
Section: Vfm Qualitative Evaluation Of Ppp Projectsmentioning
confidence: 99%